The - Jay, Antony (Oxford University Press, 2001)
The book showcases a who's who of politics, covering everyone from Napoleon to Malcolm X, Boris Yeltsin, and Bill Clinton, plus such notables as Mahatma Gandhi, Dorothy Parker, Thurgood Marshall, Rudy Giuliani, Al Gore, George Washington, Charles de Gaulle, Juan Perón, and Jean-Paul Sartre. Antony Jay covers every facet of political life--the pivotal and momentous, the sincere, the bemused, the tongue-in-cheek, and the downright rude. There are politicians' views on political events, quips about other politicians, thoughts on economics, warfare, and the state of society, as well as deeper political truths. Boxed features such as Mottoes, Newspaper Headlines, and Leaders bring related quotations together